Hellenists and Hebrews reappraising division within the earliest church - Hill, Craig C. 1957- (Minneapolis Fortress, 1992)
Includes bibliographical references and index.
Based on the author's thesis (doctoral) - University of Oxford.
Keywords: Church history -- primitive and early church, ca. 30-600.; Bible. N.T. Acts -- criticism, interpretation, etc; Bible. N.T. Epistles of Paul -- criticism, interpretation, etc